A multi-agent based optimization architecture for energy hub operation. (December 2017) - Lin, Haiyang; Wang, Qinxing; Wang, Yu; Liu, Yiling; Huang, Nianzhi; Wennersten, Ronald; Sun, Qie
Abstract: This paper proposed a novel approach to optimize the operation of an energy hub based on a multi-agent based model which includes hub element agents, a multi-energy demands agent, a commercial agent, an integrated dispatch agent and an environment agent. The novel optimization architecture is a combination and evolution of day-ahead and hour-ahead management method based on agents' pre-defined roles and their interactions. The off-design condition performance and start-stop loss of hub units are considered in the model. A simple case study is taken to enforce the optimization architecture. The results validated the efficient operation of the developed system, proving its ability to optimize the operation of energy hub.